Competitiveness of Renewable Energy Sources on the Liberalized Electricity Market in South Eastern Europe Countries - Å½ikoviÄ‡, SaÅ¡a; GrÅ¾eta, Ivan (International Journal of Energy Economics and Policy, 2017)
Although the prices of fossil fuels are at a historically low levels, geopolitics, dependence on fossil fuels, price volatility and environmental issues are among the main reasons behind the continued push for renewable energy sources. We use the levelized cost of electricity (LCOE) to calculate the economic viability of traditional power plants vs renewable energy sources. The purpose of this paper is to investigate the prices at which the selected power plants produce electricity and to compare it to the wholesale and subsidized electricity price in selected South Eastern Europe (SEE) countries – Slovenia, Croatia, Serbia and Bosnia and Herzegovina. Based on the obtained results we conclude that the renewable energy sources in SEE are still costly and deviate from the wholesale electricity prices. If SEE countries want to increase the production from renewables, they should be aware that they still cannot operate on the open market without continuous subsidies. Keywords: renewables, electricity markets, competitiveness JEL Classifications: Q20, Q28, Q30